EFFECT OF USING PROBIOTICS THROUGH DRINKING WATER ON CHARACTERISTICS OF FEMALE BALI DUCK CARCASS THAT GIVEN RATION CONTAINING GREEN BEANS SPROUTS PEELS - I G. A. P. S., Nata; Siti, N. W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2020)
This research aims to determine the effect of probiotics through drinking water on characteristics of female Bali duck carcass that given ration containing green beans sprouts peels. The research was conducted at the Sesetan Farm, Faculty of Animal Husbandry, Udayana University, on Jalan Raya Sesetan, Gang Markisa no 5 Sesetan, Denpasar City for 8 weeks. The design used was a Completely Randomized Design (CRD) consisting of 3 treatments and 5 replications, so that there were 15 experimental units. Each unit used 3 famale bali ducks with average body weight of 46,98 ± 7,18 g. The three treatments were the ducks that given drinking water without probiotics as a control (A), the ducks that given drinking water + 2.5 ml of probiotics/tail/day (B), and the ducks that given drinking water + 5 ml of probiotics/tail/day (C). The variables observed were cutting weight, carcass weight, carcass percentage, and physical composition of carcass including meat percentage, bone percentage, and percentage of subcutaneous fat including skin. The results showed that the giving of probiotics through drinking water resulted in cutting weight, carcass weight, carcass percentage, meat percentage, bone percentage, and subcutaneous fat percentage including skin which were not statistically significant (P>0.05) compared to treatment without probiotics (P0). Based on the results of this research, it can be concluded that the giving of probiotics up to 5 ml / head / day through drinking water has the same effect as without being given probiotics on the carcass characteristics of female Bali ducks which are given rations containing green bean sprouts skin waste.   Keynote: probiotics, female bali ducks, carcass characteristics and green beans sprout